Obducted ophiolites of North Island, New Zealand: origin, age, emplacement and tectonic implications for Tertiary and Quaternary volcanicity - Brothers, R.N.; Delaloye, Michel (New Zealand Journal of Geology and Geophysics, 1982)
Igrieous massifs in Northland and East Cape contain disrupted ophiolite sequences (pillow lavas, sheeted dikes, noncumulate and cumulate gabbros) with low-grade metamorphic assemblages. Sediments associated with pillow lavas, or as cappings on individual massifs, have fossils ranging in age from Early Cretaceous to Early Miocene. K-Ar ages extend from 102 to 20 Ma; an isochron age at 33.6 ± 2.1 Ma reflects argon homogenisation by plate boundary deformation at the ophiolite sites prior to obduction of the disrupted massifs during the Late Oligocene-Early Miocene. The compatibility of the fossil and radiometric ages, and the diversity of rock types (tholeiitic to alkali basalt and alkaline syenite), indicate long-continued igneous activity at localised seamounts along a nonconvergent plate boundary (transform zone) which was situated off the northeast coast of North Island and extended at least from near North Cape to East Cape. Obduction was from northeast to southwest by gravity sliding of the dismembered seamounts upon an autochthonous substrate of Permo-Jurassic greywackes and Cretaceous-Oligocene sediments. The obductive event also marked the start of midTertiary calcalkaline volcanicity in North Island. Obductive overriding of the transform zone during the latest Oligocene-earliest Miocene produced andesites along the Northland east coast, but Early Miocene-Quaternary calcalkaline belts were oriented northeast-southwest with a decreasing age for volcanism towards the Taupo Volcanic Zone. Regional tensional rifts in the latest Pliocene or Quaternary followed northwest-southeast trends.